Non-typhoidal Salmonella contamination along the pork value chain in a rural East African setting: a cross-sectional study - Gichuyia, Cianjo M.; Thomas, Lian F.; Makena, Christine; Ochieng, Linnet; Gathura, P.B.; Onono, J.O.; Fèvre, Eric M. (Oxford University Press, 2023)
Background Non-typhoidal Salmonella (NTS) is a serious foodborne pathogen that has previously been isolated from pigs presented for slaughter in a rural pork value chain in western Kenya.